A Critical Evaluation of Existing Diabetic Foot Screening Guidelines (The Review of Diabetic Studies, 2016)
AIM: To evaluate critically the current guidelines for foot screening in patients with diabetes, and to examine their relevance in terms of advancement in clinical practice, improvement in technology, and change in socio-cultural structure. METHODS: A structured literature search was conducted in Pubmed/Medline, CINAHL, Cochrane Register of Controlled Trials, and Google between January 2011 and January 2015 using the keywords ‘(Diabetes) AND (Foot Screening) AND (Guidelines)’. RESULTS: Ten complete diabetes foot screening guidelines were identified and selected for analysis. Six of them included the full-process guidelines recommended by the International Diabetes Federation. Evaluation of the existing diabetes foot screening guidelines showed substantial variability in terms of different evidence-based methods and grading systems to achieve targets, making it difficult to compare the guidelines. In some of the guidelines, it is unclear how the authors have derived the recommendations, i.e. on which study results they are based, making it difficult for the users to understand them. CONCLUSIONS: Limitations of currently available guidelines and lack of evidence on which the guidelines are based are responsible for the current gaps between guidelines, standard clinical practice, and development of complications. For the development of standard recommendations and everyday clinical practice, it will be necessary to pay more attention to both the limitations of guidelines and the underlying evidence.